Genetic Elements at the Alpha-Synuclein Locus - Prahl, Jordan; Coetzee, Gerhard A. (Frontiers in Neuroscience, 2022)
Genome-wide association studies have consistently shown that the alpha-synuclein locus is significantly associated with Parkinson’s disease. The mechanism by which this locus modulates the disease pathology and etiology remains largely under-investigated. This is due to the assumption that SNCA is the only driver of the functional aspects of several single nucleotide polymorphism (SNP) risk-signals at this locus. Recent evidence has shown that the risk associated with the top GWAS-identified variant within this locus is independent of SNCA expression, calling into question the validity of assigning function to the nearest gene, SNCA. In this review, we examine additional genes and risk variants present at the SNCA locus and how they may contribute to Parkinson’s disease. Using the SNCA locus as an example, we hope to demonstrate that deeper and detailed functional validations are required for high impact disease-linked variants.